Buffering against academic loneliness: The benefits of social media-based peer support during postgraduate study. (March 2023) - McLaughlin, Christopher James; Sillence, Elizabeth
Although the support provided by social relationships may be essential to a successful student transition, the transition to postgraduate study has had little consideration from a social support perspective. The study described in this article investigated the role played by social support in postgraduate taught students' adjustment to university, and how social media contributes to this support. Thematic analysis indicated that participants benefitted most from specialised support from peers dealing with similar academic challenges. Facebook groups showed potential as a platform for building supportive peer networks. However, the heightened visibility of communications on this platform led some participants towards Facebook Messenger as a medium for peer contact. The study suggested that, in order to meet postgraduates' needs, institutions could ensure postgraduate students have sufficient opportunity for collaboration within their cohorts. In addition, while social media may aid this process, students' individual communication preferences may inevitably influence their engagement with particular platforms.